2018
DOI: 10.1002/acr.23287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web‐Based Patient Decision Aid on Biologic and Small‐Molecule Agents for Rheumatoid Arthritis: Results From a Proof‐of‐Concept Study

Abstract: Patients' decisional conflict decreased and perceived self-management capacity improved after using ANSWER-2. Future research comparing the effectiveness of ANSWER-2 with that of educational material on biologic agents will provide further insight into its value in RA management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Our findings are in line with previous studies performed in Canadian and Dutch RA patients [15][16][17]35]. A webbased PDA for initiating DMARDs in Dutch patients with rheumatic diseases [15], including RA, ankylosing spondylitis, and psoriatic arthritis, was perceived as a helpful tool for the decision-making process and increased the number of patients who played an active role in medical decision making [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are in line with previous studies performed in Canadian and Dutch RA patients [15][16][17]35]. A webbased PDA for initiating DMARDs in Dutch patients with rheumatic diseases [15], including RA, ankylosing spondylitis, and psoriatic arthritis, was perceived as a helpful tool for the decision-making process and increased the number of patients who played an active role in medical decision making [16].…”
Section: Discussionsupporting
confidence: 90%
“…They usually include a specific section that helps patients explore their own perspective and values regarding key aspects of the decision they face [14]. Nowadays, several PDAs for RA patients are available [15][16][17][18][19][20][21][22][23]; however, none of them were developed for the Spanish population and only one was available in Spanish.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al evaluated the effects of different information formats of a decision aid for a hypothetical RA medication and found that experimental design can impact how the effects of a medication are communicated. Li et al evaluated the use of 2 online decision aids for RA patients to be used at home or in clinic: the Animated, Self‐serve, Web‐based Research tool (ANSWER) was designed for RA patients who were unsure about starting methotrexate and ANSWER‐2 was intended for RA patients who received a recommendation to start a biologic or small‐molecule agent or switch to a new one. ANSWER was evaluated using a pre/post study, with results that showed improvement in patients’ decisional conflict and knowledge and ANSWER‐2 was evaluated in a mixed‐methods, pretest/post test study with results showing that patients also had decreased decisional conflict as well as improvement in perceived self‐management capacity, but patient‐physician communication was not measured in either one.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain an objective measure of shared decision‐making, we audiotaped all visits. Thus, we were able to describe in detail how the value clarification tool impacted patient‐provider communication through review of the discussions, compared to patient‐reported outcomes measured in previous studies . In addition, the audiotapes allowed us to time the visits .…”
Section: Discussionmentioning
confidence: 99%
“…Two other randomized controlled trials are currently under way to examine the efficacy of PtDAs for people with RA who are starting or switching biologics (http://ClinicalTrials.gov Identifier: NCT02540044 and NCT02787538) (Li et al, ). The use of PtDAs for people with RA who are considering tapering and discontinuing their biologics remains to be explored but has considerable potential as a research method to explore patient perspectives, and as a clinical tool after piloting and detailed evaluation of application in this increasingly pressing scenario.…”
Section: Future Directions For Research On Tapering Biologicsmentioning
confidence: 99%